Entrepreneurial Orientation, Business Development Services, Business Environment, and Performance: A Critical Literature Review - Washington O. Okeyo; James M. Gathungu; Peter K’Obonyo (European Scientific Journal, ESJ, 2016)
The role of entrepreneurial orientation in firms has been a major area of interest to many scholars in the past. Entrepreneurially oriented firms are innovative, calculated risk-takers, and proactively reach markets ahead of their competitors. This paper examines the role of business development services, internal and external business environments on the relationship between entrepreneurial orientation and firm’s performance. The article is a theoretical discourse and uses literature from secondary sources in the analysis. The paper finds that past studies conceptualized entrepreneurial orientation as a three factor single-dimensional model and a five factor multidimensional model. Studies using the three factor model have reported different results to those adopting the five factor approach. This has led to inconsistencies in the empirical results of entrepreneurial orientation on firm’s performance. This article also finds that business development services play a mediating role in the entrepreneurial orientation and performance relationship, and that external environment moderates this relationship. However, the paper finds no role of internal environment in the EO-firm’s performance relationship. The paper concludes that the link between entrepreneurial orientation and performance is still a worthy area for further study since contradictions still exist in empirical studies. This study recommends that future studies can use a contingency framework to focus on how other factors are likely to affect this relationship.